Physical behaviour of powder ceramic part using cold isostatic pressing (CIP) processes - Md. Ani, Sarizal (2006)
Cold Isostatic Press (CIP) is mainly used for pre-forming of powder parts prior to a further densification by sintering. Isostatic pressing can apply very high pressure uniformly in all directions producing parts, which are consistent in density throughout their cross sections and highly accurate as compared to those produced uniaxially. This results in more uniform density and greater compaction. In this study the effect of CIP parameters on the shrinkage, hardness and densification behaviour of the alumina oxide powder are examined. The effect of sintering temperature on the roundness, cylindricity and surface roughness of the ceramic parts are also investigated. As a result of this study the relationship between the process parameters and the responses of alumina powder were established and can be used to produce product with the near net shape manufacturing.